Hemodynamic Effects of an Increased Midodrine Dosing Frequency. (26th April 2021) - Macielak, Shea A.; Vollmer, Nicholas J.; Haddad, Natalie A.; Nabzdyk, Christoph G. S.; Nei, Scott D.
Abstract : Objectives: In practice, midodrine has been used to reduce IV vasopressor requirements and decrease ICU length of stay. However, recent publications have failed to show clinical success when midodrine was administered every 8 hours. One possible reason for the lack of clinical efficacy at this dosing interval may be the pharmacokinetic properties of midodrine that support a more frequent dosing interval. Here, we report our institutional experience with midodrine at a dosing frequency of every 6 hours. Design: Single, quaternary academic medical center, retrospective, descriptive study. Setting: Floor and ICU patients admitted to Mayo Clinic, Rochester, from May 7, 2018, to September 30, 2020. Patients: Adult patients with an order for midodrine with a dosing frequency of "every 6 hours" or "four times daily" were eligible for inclusion. Interventions: No intervention performed. All data were abstracted retrospectively from the electronic medical record. Measurements and Main Results: Forty-four unique patients were identified that met inclusion criteria. Patients were an average of 65 years and 63.6% were male. The individual doses of midodrine ranged from 5 to 20 mg. Twenty-three patients (52.3%) were receiving IV vasopressors at the time midodrine was ordered every 6 hours. Vasopressor requirements decreased from an average of 0.10 norepinephrine equivalents 24 hours prior to the every 6-hour order to 0.05 norepinephrine equivalents 24 hours after an order for midodrine every 6 hour was placed. Conclusions: Increasing the dosing frequency of midodrine to every 6 hours may optimize its pharmacokinetic profile without compromising safety. This midodrine dosing frequency should be prospectively evaluated as a primary strategy for accelerated IV vasopressor wean.